Role of transient receptor potential (TRP) channels in osteoarthritis: a comprehensive review - Qiao, Pengyan; Wang, Wei; Liu, Sumiao; Yang, Yanli; Wang, Pingzhi; Liu, Yang; Su, Yazhen; Hu, Peng; Pan, Jie; Zhang, Liyun (Frontiers in Pharmacology, 2026)
Osteoarthritis (OA) is a chronic degenerative joint disease, primarily characterized by the degeneration of articular cartilage, synovial inflammation, and persistent pain, which severely impairs the quality of life for hundreds of millions of patients worldwide. Transient receptor potential (TRP) channels, a group of non-selective cation channels activated by various physicochemical stimuli, play a crucial role in the pathogenesis of OA. This review systematically explores the roles of the different TRP channel subfamilies, including TRPV, TRPA, TRPC, and TRPM, in OA-affected joint tissues. It highlights how TRP channels contribute to cartilage degradation and synovitis through multiple mechanisms, including the modulation of intracellular calcium signaling, the regulation of inflammatory responses, and the control of chondrocyte metabolism, apoptosis, and ferroptosis. Additionally, the critical role of TRP channels as molecular sensors of pain is discussed in detail. These channels have been shown to both mediate the initiation and transmission of nociceptive signals in sensory neurons, and to enhance pain sensitivity through interactions with immune cells. Consequently, targeting TRP channels with specific agonists or antagonists has emerged as a promising strategy for developing novel analgesics. This review outlines recent clinical progress and the therapeutic promise of targeting the TRP channel network for OA pain relief and disease modification.